1996
DOI: 10.1076/ejom.34.2.65.13021
|View full text |Cite
|
Sign up to set email alerts
|

Organisation of the Zebrafish Spinal Cord: Distribution of Motoneuron Denfrites and 5-HT containing Cells

Abstract: In order to find arguments for a selective innervation and modulation of the fast and slow spinal motoneurons in the zebrafish, we determined: the territories occupied by the dendritic trees of the large spinal motoneurons innervating the fast white muscle (WMNs) and those of the smaller motoneurons (RIMNs) innervating the slower red and intermediate fibers; the distribution of 5-hydroxytryptamine (5-HT) immunoreactive cells, which constitute one of the systems for the modulation of motoneuron activity. Motone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 0 publications
0
15
0
Order By: Relevance
“…In larval zebrafish, the major serotonergic innervation of the spinal cord originates from the raphe region, which stretches from the caudal midbrain to the anterior medulla oblongata, and there are also intraspinal neurons positive for 5-HT (McLean and Fetcho, 2004;Brustein and Drapeau, 2005). This innervation pattern persists into adulthood (Van Raamsdonk et al, 1996;Kaslin and Panula, 2001), suggesting that 5-HT responsible for the modulation of the locomotor activity may arise from intraspinal neurons as well as supraspinal projections from the raphe.…”
Section: Endogenous Release Of 5-ht In Zebrafishmentioning
confidence: 90%
See 1 more Smart Citation
“…In larval zebrafish, the major serotonergic innervation of the spinal cord originates from the raphe region, which stretches from the caudal midbrain to the anterior medulla oblongata, and there are also intraspinal neurons positive for 5-HT (McLean and Fetcho, 2004;Brustein and Drapeau, 2005). This innervation pattern persists into adulthood (Van Raamsdonk et al, 1996;Kaslin and Panula, 2001), suggesting that 5-HT responsible for the modulation of the locomotor activity may arise from intraspinal neurons as well as supraspinal projections from the raphe.…”
Section: Endogenous Release Of 5-ht In Zebrafishmentioning
confidence: 90%
“…In the spinal cord of both larval and adult zebrafish, 5-HT innervation arises from descending raphe projections and intraspinal neurons (Van Raamsdonk et al, 1996;Kaslin and Panula, 2001;McLean and Fetcho, 2004). At the larval stage, 5-HT does not affect the frequency of the spontaneous swimming and only decreases the quiescent period between consecutive swimming episodes (Brustein and Drapeau, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Our data show that the P. waltl spinal cord itself contains serotonergic perikarya, which send their axons in a plexus located on the ventrolateral surface. Intraspinal serotonergic neurons have also been found in fish (Parent and Northcutt, 1982;Ritchie and Leonard, 1982;Van Raamsdonk et al, 1996), Urodela (Gruberg and Harris, 1981;Jovanovic et al, 1996), turtle (Kiehn et al, 1992), and young opossum (DiTirro et al, 1983) but not in chameleon (Bennis et al, 1990). In mammals, 5-HT-containing intraspinal neurons were detected following pharmacological pretreatment to increase the level of 5-HT expression (Lamotte et al, 1982), whereas other studies have reported that serotonergic innervation is derived only from supraspinal structures (Kojima and Sano, 1983).…”
Section: Physiological Effect Of 5-htmentioning
confidence: 95%
“…It is unclear to what degree the cellular specificity of synaptic contacts of descending axons with the spinal motor system (Fetcho, 1992a;Van Raamsdonk et al, 1996) is reestablished. It is likely that a relatively crude reconnection with the spinal intrinsic circuitry is sufficient to produce meaningful motor output after a spinal lesion (McClellan, 1998;Bernhardt, 1999a).…”
Section: Regenerating Spinal Axons Change Their Pathway To the Gray Mmentioning
confidence: 99%